PERAN PENYIDIK PEGAWAI NEGERI SIPIL DINAS KELAUTAN DAN PERIKANAN KABUPATEN KARIMUN DALAM PENYIDIKAN TERHADAP TINDAK PIDANA PENCURIAN IKAN DI WILAYAH KABUPATEN KARIMUNBERDASARKAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Devi Wahyudi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Karimun Regency are one of Regency in Riau Archipelago Province that have a teritory of sea. Since 2009 has increase the criminal of illegal fishing in sea teritory. The illegal fishing in sea was happened in Karimun Anak sea and Malacca Strait. In 2010-2012 has registered 4 case illegal fishing and 4 case has handled by Marine and Fishing agency of Karimun Regency.The problem of this research are how the situation and condition of illegal fishing in teritory sea of Karimun, how a rules of Marine and Fishing agency of Karimun Regency in handlle illegal fishing in teritory of sea and what the obstructed by Marine and Fishing agency of Karimun Regency in handlle illegal ffishing case.This reasearc use jurisdiction empiricall methodes or sosiology law research, source of data from 3 data that: primer data, secunder data and tertier data, and technic collecting data with interview and library research after collect data then analize by qualitative to answer the research problem with deductif analize.This research have a result that rule of Marine and Fishing agency of Karimun Regency to handlle the illegal fishing in sea teritory of Karimun are to supremacy of law in sea teritory with dially patrol in sea teritory. The rule of Marine and Fishing agency of Karimun Regency was not optimally because the obstructe factor are factor human resources, medium likes a ship, factor of minim budgeting, factor of weather, factor geography of Karimun and double law enforcement. Suggestion from this research are increase the quality of Marine and Fishing agency of Karimun Regency that have basic educate from Marine, increase the ship to patrol and increase the budget for Marine and Fishing agency of Karimun Regency to promote the quality of Marine and Fishing agency of Karimun Regency.Keywords : Marine and Fishing Agency Staff – Illegal fishing – Rule